Sukuk default regulation in Malaysia and United Arab Emirates: comparative Analysis - Busari, Saheed Abdullahi; Zakariyah, Luqman; Abdul Aziz, Akhtarzaitie (IIUM Press, International Islamic University Malaysia, 2019)
The nascent Islamic finance industry is still facing the challenges of uncertainties in legal regimes, Sharī’ahinterpretations, the right of investors, and remedies in default circumstances. The event of Sukūkdefault is one of the significant challenges faced bythe Islamic capital market. The recent Dana Gas Sukūk default triggered by Sharī’ahcompliance interpretations has shown the extent of danger that moral hazards could cause to the entire Islamic finance space. Scholars have argued that the Sharī’ah-compliant arguments witnessed in the industry were because of the nature of the capital market framework of any particular jurisdiction and were not significantly Sharī’ah issues. This study aims to carry out a brief comparative analysis of the default cases in Malaysia and the United Arab Emirates (UAE). The study compares the legal jurisdiction and regulatory framework in summary-background of the judges and court decision samples based on these structures and how they have influenced Sukuk default regulations in the jurisdiction. This study employs a comparative analysis by considering fundamental elements in the regulatory framework